Novel method to achieve crystallinity of calcite by Bacillus subtilis in coupled Open Access and non‐coupled calcium‐carbon sources - Ferral-Pérez, Héctor; Galicia, Monica; Alvarado-Tenorio, Bonifacio; Izaguirre, Aldo; Aguirre-Ramírez, Marisela (2020)
Bacteria mineralization is a promising biotechnological approach to apply in biomaterials development. In this investigation, we demonstrate that Bacillus subtilis 168 induces and influences CaCO3 composites precipitation. Crystals were formed in calcium‐carbon non‐coupled (glycerol + CaCl2, GLY; or glucose + CaCl2, GLC) and coupled (calcium lactate, LAC; or calcium acetate, ACE) agar‐sources, only maintaining the same Ca2+ concentration. The mineralized colonies showed variations in morphology, size, and crystallinity form properties. The crystals presented spherulitic growth in all conditions, and botryoidal shapes in GLC one. Birefringence and diffraction patterns confirmed that all biogenic carbonate crystals (BCC) were organized as calcite. The CaCO3 in BCC was organized as calcite, amorphous calcium carbon (ACC) and organic matter (OM) of biofilm; all of them with relative abundance related to bacteria growth condition. BCC‐GLY presented greatest OM composition, while BCC‐ACE highest CaCO3 content. Nucleation mechanism and OM content impacted in BCC crystallinity.